Economía Sostenible: Retos y Oportunidades (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
The concept of sustainability implies a new philosophy of the Economy. Firstly, because it introduces the environmental consideration of economic development, and secondly, because several cases of standard economic theory are questioned.This document makes a proposal for curricular design oriented towards an Environment Economics in different areas: Economic Development; Macroeconomics principles; International Political Economy; Theory and International Trade Policy; Regional Economics; Economics of natural resources; environment accounting and social assessment of projects. In this sense, the University must help definitively consolidate the model of the Environmental Education, developing a transformative educational model of reality and at the service of all human beings and whose purposeis to train citizens aware and committed to global sustainability of the planet.
Keywords: Sustainability; Environment Economics; Environmental Education.